The Effect of Financial Literacy, Minimum Investment Capital and Investment Motivation on Students' Interest to Invest in the Capital Market with an Understanding of Investment as a Moderating Variable: Pengaruh Literasi Keuangan, Modal Minimal Investasi dan Motivasi Investasi Terhadap Minat Mahasiswa Untuk Berinvestasi di Pasar Modal dengan Pemahaman Investasi Sebagai Variabel Moderating - Aisyah Sayyidah Khansa; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of moderating variables on Understanding Investment in Financial Literacy, Minimum Investment Capital and Investment Motivation on Student Interest to Invest in the Capital Market. The sample in this study was 100 respondents by distributing 100 questionnaires to Accounting Students, UMSIDA. By using data analysis techniques in the form of Outer Model for testing the validity and reliability of the data and Inner Model for hypothesis testing, using the SmartPLS version 3.0 application. The results in this study prove that Financial Literacy and Minimum Investment Capital cannot be moderated by Investment Understanding on Student Interest to Invest in the Capital Market. This is different from Investment Motivation which can be moderated by Investment Understanding. So that it can strengthen the relationship between Investment Motivation and Student Interest to Invest in the Capital Market.